TINGKAT PENGETAHUAN, SIKAP DAN PERILAKU TENTANG RESISTENSI ANTIBIOTIK PADA SISWA MADRASAH ALIYAH NEGERI 3 BANYUWANGI, INDONESIA - Endraswari, Pepy; Koendhori, Eko Budi; Kusumaningrumm, Deby; Muna, Nafdzu Mahmudatul (Jurnal Abdi Insani, 2024)
Microbial resistance to antimicrobials, especially antibiotics, has become a global health problem with various adverse impacts. Studies show that resistance to antibiotic drugs increases directly proportional to the number of increases in their consumption. This happens due to the irrational use of antibiotics and inadequate public education. The high incidence of antibiotic use is due to the lack of counseling in the community to increase knowledge and awareness about the wise use of antibiotics. This community service aims to see how the level of knowledge of senior high school students (MAN 3 Banyuwangi) about antibiotic resistance. This community service design is counseling 90 grade XI students and primary data was collected directly from a questionnaire before and after counseling. The evaluation of the questionnaire before and after the counseling showed that educational and counseling activities about antibiotic resistance increased the knowledge of students participating in the counseling at MAN 3 Banyuwangi. It can be concluded that effective educational interventions are essential, including interventions through counseling activities such as community service activities, to improve student understanding so that high school students can play a role in controlling antibiotic resistance.